THE VELOCITY OF COUNTERMOVEMENT JUMP IMPROVE THE PERFORMANCE JUMP IN HEALTHY ATHLETES - Carlos De la Fuente; Hugo Henriquez; Andrés Fuentealba; Roberto Peña y Lillo; Rodrigo Ramírez- Campillo (Sport Scientific And Practical Aspects, 2025)
Jump performance is of interest in many sports disciplines and after injuries, but many mechanical features could be extracted from a force platform being confusing to understand which mechanical variable could be more related to the high achieved. This knowledge may permit optimization jump skills during training periods. Therefore, we determine the associations between mechanical variables of the center of mass and the height jump during unweight and propulsion phases in countermovement jump in amateur healthy young Athletes. Thirty-six subjects (aged 20.6 ± 2.9 years-old and body mass index of 21.9 ± 2.2 Kg/m2) were included. A jump assessment using a Bertec® force platform was performed obtaining the mean, minimum, maximal and range of vertical ground reaction force, position, velocity, acceleration, impulse, power, and rate of force development for unweighting and propulsion phase during the countermovement jump. A correlation analysis with a type I error of 5% was performed. The main finding was that healthy young athletes showed a moderate association between the height of the jump and minimal velocity during unweight phase of countermovement jump, but also during the propulsive phase existed a very high association between the height of the jump and the maximal velocity during propulsion phase (p<0.001). In healthy young athletes, the maximization of velocity execution of triple-flexion during the unweighting phase and the development of a triple-extension with maximal velocity during the propulsion phase are the most important mechanical features to improve the countermovement jump.